Influence of Certain Animal Manures on Incidence of Stem Canker and Black Scurf Disease on Potato - Heidi I.G. Abo-Elnaga; A.A. Mohamed; M.M. El-Fawy; A.M. Amein (Journal of Basic & Applied Sciences, 2012)
Rhizoctonia solani (Kuhn) is the causal pathogen of stem canker and black scurf disease on potato. Under open greenhouse conditions two isolates of R. solani (AG-3) were used to infect Nicola potato cultivar and caused typical symptoms of stem canker and black scurf disease with different disease severities ranged from strong to weak. In vitro Addition of chickens, pigeons and cows manure extracts to the media at different concentrations 0-50% (vol/vol) reduced the growth of the tested isolates of the pathogen. The highest reduction of mycelial growth of the pathogen isolates was obtained when pigeons manure extract was added to the growing media at a concentration of 50 % (vol/vol) followed by another concentrations. Under open greenhouse conditions during two growing seasons 2010 and 2011 addition of manures to the soil at 0.5 and 1% weight of the soil before sowing significantly decreased incidence of stem canker and black scurf disease. Generally, cow manure showed the highest effect on controlling the disease followed by pigeons and chickens. On the other hand, concentration 1 % of all manures was more effective on the reducing of disease incidence than the concentration 0.5 %. On the other hand, cow manure was more effective in increasing the eyes germination followed by pigeons and chicken manure and decreased the dead of sprouts, stem canker and black scurf. Treatment with all the kinds of tested manures increased eyes germination of tubers and reduced sclerotia formation on the surface of tubers and hence disease incidence.